TEACHERS’ PERCEPTION TO CLIL AND WEB-BASED MATERIAL IMPLEMENTATION IN A PRIMARY SCHOOL - Alimin Adi Waloyo; Khoiriyah Khoiriyah; Rafika Rabba Farah (University of Kuningan, 2021)
Primary school teachers have a crucial role to support CLIL and web-oriented media implementation in class. CLIL approach pedagogically offers double advantages; English competence and content development. This pedagogical approach leads to sufficient English input at the early stage of learning which makes primary learners able to shift the paradigm that English is a challenging language to learn. More importantly, primary school learners can take the advantages of the Information and Communication Technology (ICT) part of their daily use for the sake of CLIL, so learning can be fun and enjoyable. Nevertheless, much of the previous research in Indonesian context gives limited attention to how primary school teachers perceived CLIL interwoven into ICT based media.) that situation led into this research. Also, this research is expected to encourage the CLIL application in formal education, particularly in primary levels due to time efficacy and effectiveness. The involved participants were 12 primary school teachers in a primary school in Malang. A 14-item Likert-Scale questionnaire and FGD were applied to collect the data. It was found that the teachers perceive the CLIL and web-based media positively, but they would reconsider to implement it in their class due to English competency reasons and material design issue, facilities, and school support. Therefore, hybrid CLIL implementation and teachers’ collaboration are suggested.